(untitled) - Devito, Joseph A. (Boston, 2004)
Provides a highly interactive presentation of the theory, research, and skills of interpersonal communication with strong, integrated discussions of diversity, ethics, workplace issues, and technology. Recognized for its ability to help students understand the crucial connection between theory and practice, the Tenth Edition presents a comprehensive view of the theory and research in interpersonal communication and, at the same time, guides students to improve a wide range of interpersonal skills and to apply these to personal, social, and workplace relationships. Superior coverage of cultural diversity, ethics, interpersonal communication in the workplace, and the workings and effects of technology make The Interpersonal Communication Book the best choice for preparing students to communicate successfully in today's world.
Keywords: Interpersonal communication